The effect of love of money and Machiavellian on accounting students’ ethics perception / Muhammad Alif Maggalatta and Desi Adhariani - Maggalatta, Muhammad Alif; Adhariani, Desi (Faculty of Accountancy, 2019)
The purpose of this study is to understand the effect of Love of money and Machiavellian on ethics perceptions of accounting students. The knowledge attained from this study will allow lecturers and academicians to better form the methods in teaching ethics in accounting, through the evaluation of Love of money and Machiavellian. This research uses survey and quantitative analysis. The data were collected by distributing offline and online questionnaires to students in a university in Indonesia. The result show that love of money and Machiavellian are both negatively affecting the ethical perception. The practical implication of the research is the need to inform students on the negative impact of the love of money and Machiavellian on ethics; and required steps to overcome such negative impact by inserting ethics materials in several accounting courses. Accounting students represent the future accountants and the highly ethical accountants will protect the profession and society from harmful consequences of unethical accounting and business practices.